Beyond Planning: The Implementation of a Worksite Health Promotional Scheme - Bjørnstad, Thor Christian; Steen-Johnsen, Kari (Nordic Journal of Working Life Studies, 2012)
The aim of this article is to provide insight into how the presence of diverging organizational logics influences the outcome of worksite health promotion projects. The study is based on a one-year qualitative single-case study of the implementation of a health promotional physical exercise program in a transnational transport and logistics company based in Norway. While the program that was implemented was based on dominant logics in Norway, i.e., the emphasis on worker participation and influence, the organizational logics of the transport company defined company–worker relationships in other terms. We found that the logic of a highly specialized work organization that combined strict work distribution with a set of narrowly defined work tasks contradicted the logic that underpinned the health promotional program, and that this contradiction is an important reason why the initiative failed. We therefore conclude that in implementing health promotion projects at the workplace, there is a need to observe the relationship between logics related both to the project and to the organization.